The Implementation of Zakat Fatwas in Amil Zakat Institutions: An Analysis of Opportunities and Challenges - Nasution, Erni Juliana Al Hasanah Al Hasanah (SCAD Independent, 2025)
The issue of zakat fatwa implementation faces challenges in ensuring sharia compliance and effective governance. This study examines zakat fatwa implementation in three institutions: Muhammadiyah Amil Zakat Institute (LAZISMU), Nahdlatul Ulama Amil Zakat Institute (LAZISNU), and the Islamic Dakwah Fund (IDF) of the Council of Indonesian Ulama (MUI). Using a mixed-methods approach with a sequential explanatory design, the research explores the application of zakat fatwas issued by Muhammadiyah, Nahdlatul Ulama (NU), and MUI, their impact on institutional compliance, and the opportunities and challenges involved. Quantitative data from 40 zakat administrators (amil) and qualitative insights from eight key informants were analyzed using regression models, the Public Satisfaction Index (IKM), and thematic qualitative techniques. Results indicate zakat fatwa implementation is “suboptimal”, with an Amil Satisfaction Index of 74.60. Opportunities include digitalization, institutional collaboration, and standardized management, while challenges involve limited skilled human resources, insufficient professional certification, and inadequate fatwa dissemination. The study underscores the need for improved fatwa dissemination, systematic SOP evaluations, and enhanced amil professionalism. These findings contribute to the global discourse on zakat governance by offering insights from Indonesia’s multi-fatwa system, which has implications for similar institutions worldwide. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back //